Luminescence studies for energy transfer of lead sulfide QD films. Issue 54 (17th May 2016) - Wang, Joanna S.; Ullrich, Bruno; Das, Anirban; Wai, Chien M.; Brown, Gail J.; Dass, Chandriker K.; Hendrickson, Joshua R.
Abstract : PbS QDs of different sizes are deposited with supercritical fluid CO2 to form laterally uniform PbS QD films as compared to other deposition methods. Luminescence studies show FRET process and different transient life times. Abstract : Lead sulfide (PbS) quantum dots (QDs) of different sizes are deposited with supercritical fluid CO2 (sc-CO2 ) to form laterally uniform PbS quantum dot films on glass substrates as compared to other deposition methods. Fluorescence and photoluminescence (PL) spectra of PbS QDs obtained from these closely packed films prepared by the sc-CO2 method reveal effective Förster resonance energy transfer (FRET) between PbS QDs of two different sizes, while the films composed of three different sizes of PbS QDs show an even more effective FRET from the smallest to the largest particles. The FRET measured by PL is consistent with that measured by fluorescence spectroscopy at room temperature. From the PL studies of PbS QD films containing two different QD sizes, we demonstrate that the occurrence of FRET under cryogenic conditions is more efficient.